Effect of β-blockade on lung function, exercise performance and dynamic hyperinflation in people with arterial vascular disease with and without COPD. Issue 1 (5th April 2017) - Key, Angela; Parry, Matthew; West, Malcolm A; Asher, Rebecca; Jack, Sandy; Duffy, Nick; Torella, Francesco; Walker, Paul P
Abstract : Introduction: β Blockers are important treatment for ischaemic heart disease and heart failure; however, there has long been concern about their use in people with chronic obstructive pulmonary disease (COPD) due to fear of symptomatic worsening of breathlessness. Despite growing evidence of safety and efficacy, they remain underused. We examined the effect of β-blockade on lung function, exercise performance and dynamic hyperinflation in a group of vascular surgical patients, a high proportion of who were expected to have COPD. Methods: People undergoing routine abdominal aortic aneurysm (AAA) surveillance were sequentially recruited from vascular surgery clinic. They completed plethysmographically measured lung function and incremental cardiopulmonary exercise testing with dynamic measurement of inspiratory capacity while taking and not taking β blocker. Results: 48 participants completed tests while taking and not taking β blockers with 38 completing all assessments successfully. 15 participants (39%) were found to have, predominantly mild and undiagnosed, COPD. People with COPD had airflow obstruction, increased airway resistance (Raw) and specific conductance (sGaw), static hyperinflation and dynamically hyperinflated during exercise. In the whole group, β-blockade led to a small fall in FEV1 (0.1 L/2.8% predicted) but did not affect Raw, sGaw, static or dynamic hyperinflation. No difference in response to β-blockade was seen in those with and without COPD. Conclusions: In people with AAA, β-blockade has little effect on lung function and dynamic hyperinflation in those with and without COPD. In this population, the prevalence of COPD is high and consideration should be given to case finding with spirometry. Trial registration number: NCT02106286.